Debt-reducing exchange offers - Lie, Erik; Lie, Heidi J; McConnell, John J (Journal of Corporate Finance, 2001)
Announcements of debt-reducing exchange offers are associated with a negative average stock price reaction. We address two questions: Why do firms undertake debt-reducing exchange offers? And, what is the information conveyed by such offers? The answers are interrelated: Debt-reducing exchange offers are undertaken by financially weak firms in an effort to stave off further financial distress and, thereby, preserve value for shareholders. A successfully completed exchange offer significantly reduces the likelihood that a firm will enter Chapter 11. Announcements of debt-reducing exchange offers apparently contain two pieces of information: (1) the firm is financially weaker than would have been apparent from other publicly available information, and (2) management is attempting to preserve value for shareholders.